O direito educacional brasileiro: uma análise das ações da AMSOP e a relação com a melhoria da qualidade da educação no sudoeste do Paraná - Oliveira, Ana Paula (2021)
The objective of the dissertation is to analyze the actions of the Association of Municipalities in the Southwest of Paraná (AMSOP) and its relationship with the improvement of the quality of education in the Southwest of Paraná. The research structure is divided into three chapters. The first chapter includes two items. Initially, considerations about the State, Democratic State and Democratic Rule of Law. This is justified, therefore, the quality of education in the municipalities served by AMSOP, will be analyzed from the perspective of this process, which is given by the achievements and rights, which are the responsibility of every citizen. Then, the attempt is to identify the concept of teaching quality in CF / 88 and in the UNESCO / 1997 Quality and Equity Report. This is necessary for us to understand how AMSOP's actions, as a civil entity, come close to the legal principles set out in the larger legislation. The second chapter entitled “AMSOP's historical approach in Southwest Paraná” is organized into two topics. First history of the creation of AMSOP and its advances in the last 20 (twenty) years. Then the general objectives of the institution will be addressed. The third and last chapter, presents 5 (five) basic items in its structure. The first item contemplates AMSOP and the structuring of policies in the Southwest of Paraná through programs and documents created by the entity, aimed at the development of the territory of the Southwest of Paraná. Following, the organization and relevance of the “Pacto Nova Itália” program - PNI, Forums, Conference in the search for development and human formation for the region are exposed. In the third item, we present the Cartas do Sudoeste, a document created by AMSOP aimed at meeting regional priorities. The fourth item presents the entity's actions aimed at valuing intra- and extra-school factors as pathways to educational advancement in the Region; and to conclude the chapter, in the fifth item, we address the role of AMSOP in improving the quality of education in the Southwest of Paraná and present considerations from the IDEB of the municipalities within the 12-year period, that is, the years 2007 to 2019. The research is expected to contribute to a cyclical look at AMSOP's actions, and the way in which they interfere in the regional and educational development of that region.